Analysis of an invented writing system for the Shanghainese language - Simpson , Logan (Investigationes Linguisticae, 2020)
The present study uses qualitative methods to analyze and restore an invented missionary writing system for the Shanghainese language, and uses the restoration to check for historical sound change. The project consists of two parts: the analysis and restoration of the orthography and the confirmation of historical sound changes in Shanghainese. The restoration of the writing system provides all symbols with equivalent International Phonetic Alphabet (IPA) symbols. Following the restoration to IPA is an explanation of the rules for combining initial and final symbols to form a single character, as well as rules for tonal distinction. The analysis of the restored orthography compares its development with the academic criteria for orthography development, and finds that it is a sound writing system. The evaluation also reviews the sociolinguistic criteria crucial for orthography acceptance, and shows that the writing system does not meet these criteria in present day Shanghai. The results of the check for historical sound change confirm that many of the sounds not found in present day Shanghainese existed in this writing system. The phones found in this writing system are able to confirm the disappearance or merger of various sounds in Shanghainese since the mid 19th century. Overall, the study shows that the invented writing system is sound, but would not be accepted in Shanghai today. However, it should be reviewed by other linguists as having the possibility to represent other languages.